Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

Multi-Year Predictability of Sandy Shoreline Change from Remote-Sensing Reconstruction and a Spatiotemporal Transformer - Keyu Tao; Fenzhen Su; Fengqin Yan; Vincent Lyne; Jiaojie Zhang (Journal of Marine Science and Engineering, 2026)
Most studies of sandy shoreline forecasting address relatively short time scales. Under limited annual observations and strong shoreline persistence, the added value of a Transformer over simple baselines and the influence of remotely sensed shoreline definitions remain insufficiently tested. Using Xichong Beach, Shenzhen, we constructed 40-year shoreline series for 80 transects from 284 quality-controlled Landsat waterlines acquired during 1986–2025. We compared a quality-controlled annual landward-envelope composite waterline with annual median waterlines and examined the effects of transect spacing and positional error on long-term change rates. We then developed a residual spatiotemporal Transformer that uses 10 years of shoreline states and historical wind–wave exposure to directly predict five future horizons, and compared it with persistence, rolling linear trend, and random forest models. The annual landward-envelope composite waterline was systematically landward of the annual median waterline (positional RMSE, 12.78 m), but their alongshore LRR patterns were strongly correlated (r = 0.982) and identified consistent major erosion–accretion zones. After Monte Carlo error propagation, the beach-mean LRR was −0.250 m yr−1 (95% interval, −0.299 to −0.203 m yr−1), whereas the direction of change remained uncertain at 39 local transects. Across 400 year–transect locations in the independent 2021–2025 evaluation period, the Transformer produced the lowest RMSE, MAE, and Dynamic RMSE (9.403, 7.399, and 12.042 m, respectively), with an RMSE skill of 27.0% relative to persistence. Environmental features yielded a small gain during rolling validation but no stable improvement in the independent evaluation period. SHAP attribution identified recent shoreline state as the dominant predictive information, followed by wind–wave exposure. Direct forecasts for 2026–2030 gave a beach-mean displacement of −8.527 m in 2030 (95% conditional residual bootstrap interval, −12.514 to −4.950 m), although every local-transect interval crossed zero. Multi-year predictability is therefore scale dependent: beach-mean trends are more resolvable, whereas local change directions remain constrained by observation error and model residuals.

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Triploid induction by hydrostatic pressure in female Megalobrama amblycephala × male Culter alburnus hybrids: effects on somatic growth enhancement and sterility - Zaozao Guo; Lianghua Zhang; Chao Ren; Keyu Su; Xiangsheng Yu; Guodong Zheng; Shuming Zou (Aquaculture, 2026)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

The modulation of proteomics and antioxidant stress is involved in the effect of nitazoxanide against Japanese encephalitis virus in vitro - Yu Su; Yanping Wang; Chengeng Xiong; Xiaoyang Wang; Chunmei Wang; Wen Zhou; Donghai Zhou; Keyu Zhang (Veterinary Microbiology, 2024)

Effects of seasoning addition and cooking conditions on the formation of free and protein-bound heterocyclic amines and advanced glycation end products in braised lamb - Qiaochun Chen; Keyu Lu; Jiayi He; Qian Zhou; Siqian Li; Hui Xu; Yuting Su; Mingfu Wang (Food Chemistry, 2024)

A stronger association of mental disorders with smaller particulate matter and a modifying effect of air temperature - Keyu Wu; Junwen Tao; Qiyue Wu; Hong Su; Cunrui Huang; Qingrong Xia; Cuizhen Zhu; Jing Wei; Min Yang; Junwei Yan; Jian Cheng (Environmental Pollution, 2024)

Seasonal peak and the role of local weather in schizophrenia occurrence: A global analysis of epidemiological evidence - Jihong Hu; Yufan Feng; Hong Su; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Keyu Wu; Mohammad Zahid Hossain; Yunquan Zhang; Kejia Hu; et al. (Science of The Total Environment, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)